Freud - Lear, Jonathan (London : Routledge, 2015)
In this thoroughly updated second edition, the author offers a clear introduction to and analysis of Freud's ideas, emphasizing the philosophical areas where his influence remains significant. These include the philosophy of mind, free will and determinism, rationality, the nature of the self and subjectivity, as well as ethics and religion.
Includes bibliographical references and index.
Keywords: Freud, Sigmund, 1856-1939.; Psychoanalysis and philosophy; Psychoanalysts - Austria - Biography